Knowledge, Attitude, and Practice Survey of Gastroparesis in Asia by Asian Neurogastroenterology and Motility Association - Oshima, Tadayuki (KOREAN SOC NEUROGASTROENTEROLOGY & MOTILITY, 2021)
10.5056/jnm20117